(untitled) (Encuentros, 2020)
This paper will review the different existing literature on studies of international relations in Latin America, specifically in Colombia will be reviewed. As a subject little explored by the scholars, this effort is a great contribution to the development of future research to account for the development of the discipline of international relations. Also, through this historic journey will be known about the background that led to the emergence and evolution of international studies in the region. Key words: Latin America, International Studies, International Relations, Sociology of Science. Referencias Ardila Martha (1991). Los estudios sobre relaciones internacionales en las universidades colombianas. En: Ardila Martha, Cardona Diego, Maira Luis y Tokatlian Juan. Los estudios sobre relaciones internacionales en Colombia y América Latina. Documentos de trabajo. Instituto de estudios políticos y relaciones internacionales, serie documentos de trabajo No. 2, pp. 17-20. Borda Sandra (2007). El estado de los estudios internacionales en Colombia. Reporte de Investigación. Presentado al Grupo de Expertos en Relaciones Internacionales convocado por Colciencias. Collins Randall (2005). Sociología de las filosofías. Una teoría global del cambio intelectual. Barcelona: Editorial Hacer. Lechini Gladys (2009). La Cooperación Sur-Sur y la búsqueda de autonomía en América Latina: ¿Mito o realidad? En: Revista Relaciones Internacionales, No. 12, GERI-UAM, octubre de 2009, pp. 55-83. Merton Robert K. (1977). La sociología de la ciencia: investigaciones teóricas y empíricas. Recopilación e introducción de Norman W. Storer. Madrid: Alianza Editorial Orrego Vicuña Francisco (1989). Los estudios internacionales en América Latina. Realizaciones y desafíos. Chile: Instituto de Estudios Internacionales de la Universidad de Chile. Pardo Rodrigo y Tokatlian Juan Gabriel (1988). Teoría y práctica de las relaciones internacionales: el caso de Colombia. En: Documentos Ocasionales del Centro de Estudios Internacionales de la Universidad de Los Andes. Perina Rubén (1985). El estudio de las relaciones internacionales en América Latina y El Caribe. Argentina: Grupo Editor Latinoamericano, pp. 199-223. Ramos Amalin(2001). Relaciones internacionales en Colombia 2002-2010: tendencias teóricas y repercusiones prácticas. Trabajo de grado para optar al título de Magíster en Relaciones Internacionales. Universidad de Buenos Aires, Argentina. Rangel Alfonso (1989). La educación internacional en América Latina. En: Foro Internacional, Vol.30, No. 1(117), julio-septiembre, pp. 153-168. Schmidt Brian. The political Discourse of Anarchy (1998). USA: State University of New York Press, pp. 309. Tickner Arlene (2001). Un estado del arte de los estudios internacionales en América Latina. Centro de Estudios Internacionales. Departamento de Ciencia Política, Universidad de Los Andes. Tickner Arlene (2002). Los estudios internacionales en América Latina ¿Subordinación intelectual o pensamiento emancipatorio? Colombia: Alfaomega, pp. 236. Tickner Arlene (2003). Hearing Latin American Voices in International Relations Studies. En: Revista International Studies Perspectives, 4, pág. 325-350. Tickner Arlene (s.a.). Relaciones de conocimiento centro-periferia: hegemonía, contribuciones locales e hibridización. Tickner Arlene (2008). Latin American IR and the Primacy of lo práctico. En: Revista International Studies Review, 10, pág. 735-748. Tickner Arlene (2009). Latin America Still policy dependent after all these years. En: WaeveR Ole y Tickner Arlene (2009). International Relations scholarship around the world. Estados Unidos: Routledge, pp. 32. Tickner Arlene y Borda Sandra (2011). Relaciones Internacionales y política exterior de Colombia. Colombia: Ediciones Uniandes, pp. 46. Tokatlián Juan Gabriel (1991). La teorización de las relaciones internacionales en Colombia. En: Ardila Martha, Cardona Diego, Maira Luis y TOkatlián Juan. Los estudios sobre relaciones internacionales en Colombia y América Latina. Documentos de trabajo. Instituto de estudios políticos y relaciones internacionales, serie documentos de trabajo No. 2, pp. 21-22. Tomassini Luciano (1985). Los estudios internacionales en América Latina: una experiencia regional. En: PERINA Rubén. El estudio de las relaciones internacionales en América Latina y El Caribe. Argentina: Grupo Editor Latinoamericano, pp. 199-223. Turton Helen (2013). The sociology of a diverse discipline: International Relations, American Dominance and Pluralism. Thesis for the degree of Doctor of Philosophy in Politics. University of Exter. UNIVERSIDAD DE LOS ANDES (2012). Enseñanza, Investigación y Política Internacional. En: Documentos del Departamento de Ciencia Política No. 19, pp. 33. Waever Ole (1998). The sociology of a Not So International Discipline: American and European Developments in Intenational Relations. En International Organization, volume 52, issue 04, autumn, p. 687.727. Waever Ole y Tickner Arlene (2009). International Relations scholarship around the world. Estados Unidos: Routledge, pp. 350.